2021
DOI: 10.3390/su13074047
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Evaluation in Education from the Sustainability Perspective: A Review of the Scientific Literature

Abstract: (1) Background: This paper outlines the results of a literature review of meta-analyses published on motivation and evaluation in the last five years. (2) Methods: A systematic review of three educational databases (WoS, SCOPUS and ERIC) was conducted following the PRISMA and PICO approaches. A total of 54 peer-reviewed meta-analysis papers were selected, analysed and compared. (3) Results: A significant number and variety of meta-analyses have been conducted: motivation meta-analyses focus primarily on contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
(11 reference statements)
2
3
0
Order By: Relevance
“…Although other readings were picked up, these were only applied to facilitate comprehension, application, analysis, and evaluation of the arguments presented, and hence they are not reflected in the key research article sample shown in Figure 1. This is consistent with similar research conducted by Tsalis et al [27], who argues that such a process seeks to create a customised and contextualised but open-minded perception of issues typical of qualitative research justifying the key criteria applied for the selection of articles focused on research reports related to SA [25,26]. Substantiating the qualitative analysis of the literature review, it is important to identify the themes created, which included human, social and economic development in SA, sustainable food production and food consumption entrepreneurship, innovative digital entrepreneurship development (see Table 1.).…”
Section: Research Processsupporting
confidence: 85%
See 1 more Smart Citation
“…Although other readings were picked up, these were only applied to facilitate comprehension, application, analysis, and evaluation of the arguments presented, and hence they are not reflected in the key research article sample shown in Figure 1. This is consistent with similar research conducted by Tsalis et al [27], who argues that such a process seeks to create a customised and contextualised but open-minded perception of issues typical of qualitative research justifying the key criteria applied for the selection of articles focused on research reports related to SA [25,26]. Substantiating the qualitative analysis of the literature review, it is important to identify the themes created, which included human, social and economic development in SA, sustainable food production and food consumption entrepreneurship, innovative digital entrepreneurship development (see Table 1.).…”
Section: Research Processsupporting
confidence: 85%
“…A reflective analysis of trends, linkages, propositions, and concepts emerging from the themes was thereafter used as a basis for the design of the conceptual model. This is homogenous with conceptual studies, as reflected in similar research by Sanchez-Satamria et al [26]. The review of the research articles used a qualitative methodological stance that is appropriate for pursuing a detailed, in-depth analysis of issues.…”
Section: Research Processmentioning
confidence: 99%
“…Similarly, mentors motivate mentees to attend the exams, and all of this seems to have an impact on the results. These strategies offer a motivational component to the mentees, in line with the suggestion of previous studies (Prieto, 2020;Sánchez-Santamaría, et al, 2021).…”
Section: Mentoring and Academic Performancesupporting
confidence: 77%
“…One of the most studied variables in relation to academic performance has been intelligence (González-Benito et al, 2021). Motivational components have also been found to determine academic performance (Prieto, 2020;Sánchez-Santamaría et al, 2021). Additionally, academic performance in university environments has been considered negatively correlated with university dropout (Maluenda-Albornoz et al, 2022).…”
Section: Academic Performancementioning
confidence: 99%
“…This is combined in this research with the intention of obtaining evidence to gain a better understanding of the implications of an educational process in postgraduate teacher education. As noted in other work [53]: "A quality education inspired by the social value of sustainability can be defined as one that is able to provide meaningful and relevant learning environments, processes and tools for all learners, ensuring access, promoting retention and contributing to educational success for all in line with SDG 4 of the 2030 Agenda framework: ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all [54]". In addition, as previously stated, this research aims to create conditions and processes to improve learning in an educational context of heightened social vulnerability, so that participants may develop strategies and engagement skills to foster successful education for all.…”
Section: Discussionmentioning
confidence: 99%